Extent of thermal stress in newborns in maternity wards and factors affecting it - Ojha, Sakshi; Verma, Yogendra S. (International Journal of Contemporary Pediatrics, 2018)
Background: The objective was to assess thermal stress in newborns on mother side in maternity wards and various neonatal and maternal characteristics affecting it. Methods: It was a Hospital based analytical study carried ou at Maternity ward of Medical College Hospital (Tertiary health center) and Maternity ward of Prasutigrah under department of health (Primary health center) in central part of India. Participants were 960 neonates on mother side in maternity wards (480 in each health center) upto first seven days of life (168 hours) were studied for a duration of one year. Newborns were enrolled twice a week alternatively in the two health centers throughout the year. Various neonatal and maternal characteristics of the enrolled newborns were noted as per the proforma and neonatal body temperature was recorded. Results: Almost half of the newborns (47.08%) were found in thermal stress. More than one third (37%) were hypothermic and 9.4% were hyperthermic. Incidence of hypothermia found in primary health center (44.4%) was significantly higher than in tertiary health center (30.8%) (P<0.001). Incidence of hyperthermia was nearly same (9.4-9.6%). Hypothermia was more in pre terms (P = 0.031), in neonates of mothers belonging to lower socioeconomic status (P =0.049), in neonates of young mothers with age <25years (P=0.011), when breastfeeding was delayed (>1 hour) (P=0.006) and when cloth score was <5 in coldest quarter of the year, (November to February) (P<0.001=). No significant correlation was seen with hyperthermia and above factors. Conclusions: No significant correlation was found with maternal literacy, parity, mode of delivery, frequency of breastfeeding, birth weight, oil application, proximity with mother, sex and age of the baby.